(untitled) (New York, 1995)
The "notorious" uncensored Smithsonian Enola Gay exhibit script, as well as author's attempt to set the record straight
Keywords: World war,World war,Atomic bomb,United States; Moral and ethical aspects,Military policy,Moral and ethical aspects; 1939-1945,1939-1945; Japan,Hiroshima-shi,Japan,Nagasaki-shi